2019
DOI: 10.3389/fpsyt.2019.00817
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adherence to Treatment in Behavioral Health Therapy for Latino Immigrants: The Importance of Trust

Abstract: A complex array of barriers to care influence patients' adherence to behavioral healthcare services. Understanding barriers to care is critical to ensure sufficient dosage of treatment. This study assessed the influence of perceived barriers on Latino migrants' prospective adherence to treatment for co-occurring mental health and substance use disorders as part of a clinical trial. Eligible participants (18–70 years-old) were recruited from community-based settings and classified according to their interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…44,45 This could be attributed to difficulty in developing trust in mental health and addiction services due to unfamiliarity with how these services work 31,46 and previous negative experiences with treatment. 35 Moreover, participants revealed that the situation worsened when they had to wait longer to start treatment, leading to more substance use and relapses, which is reported by Pinedo et al 36 as a logistical barrier to treatment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…44,45 This could be attributed to difficulty in developing trust in mental health and addiction services due to unfamiliarity with how these services work 31,46 and previous negative experiences with treatment. 35 Moreover, participants revealed that the situation worsened when they had to wait longer to start treatment, leading to more substance use and relapses, which is reported by Pinedo et al 36 as a logistical barrier to treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Understanding barriers is critical to ensure lower drop-out rates and facilitate adequate use of treatment. 35 The participants stated that receiving treatment from culturally competent HPs facilitated their treatment process, as their needs were understood during the counseling and healing process. This finding is consistent with previous studies 44,52 and a review, 53 where having HPs that were sensitive to cultural nuances was seen as more effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the adequate use of available treatment and to ensure lower drop-out rates, it is critical to understand the barriers. 65 PCH 35 and a cultural competence approach 40 have been shown to facilitate treatment engagement. According to the framework suggested by Saha et al, 43 both PCH and cultural competence have overlapping core values that work at the interpersonal level (between health professionals and users) and the health system level.…”
Section: Discussionmentioning
confidence: 99%
“…An observation should be made regarding the name of the medication used in the public service, in which the generic name of the active ingredient is prescribed by the doctor avoiding the brand name, which may hinder memorization. Dosage change is another result that must be considered because the partial or total non-compliance of the dosage regimen is one of the main barriers to effective drug treatment, especially chronic use medication, leading to aggravations with negative repercussions on the user's quality of life and increased costs to the health system (Falgas-Bague et al, 2019). However, this finding draws attention to the discovery that this change is made mainly by those with a higher level of education, which is not aligned with the general consensus that warns that low education interferes negatively with the understanding of the prescription.…”
Section: Discussionmentioning
confidence: 99%